1996
DOI: 10.1002/(sici)1097-0215(19960807)67:4<498::aid-ijc6>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma, myeloma and occupation: Results of a case-control study

Abstract: The known risk factors for lymphoma and myeloma cannot account for the current incidence rates of these cancers, and there is increasing interest in exploring occupational causes. We present results regarding lymphoma and myeloma from a large case-control study of hundreds of occupational exposures and 19 cancer sites. We examine in more detail those exposures previously considered to be related to these cancers, as well as exposures which were strongly related in our initial analyses. Lymphoma was not associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…Our finding of an increased risk of myeloma for several metal work-related occupations is consistent with the results of several other studies (30,(47)(48)(49)(50)(51)(52). There is only limited information about exposure to specific metals and multiple myeloma.…”
Section: Baris Et Alsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of an increased risk of myeloma for several metal work-related occupations is consistent with the results of several other studies (30,(47)(48)(49)(50)(51)(52). There is only limited information about exposure to specific metals and multiple myeloma.…”
Section: Baris Et Alsupporting
confidence: 92%
“…We found elevated OR values for several occupations that had been previously reported, such as timber cutting and related occupations (20), plumbers, pipefitters and steamfitters (17,20), painters (20,44,45), food and beverage preparation workers (17), health and science technicians (46), and janitors and cleaners (47). Our finding of an increased risk of myeloma for several metal work-related occupations is consistent with the results of several other studies (30,(47)(48)(49)(50)(51)(52).…”
Section: Baris Et Alsupporting
confidence: 91%
“…When solvents were evaluated as a general category, most studies observed nonsignificant positive associations with NHL risk, 20,21,29,71,105,118,129,170,202 and 2 reported inverse associations. 114,142 No association between occupational exposure to organic solvents and lymphatic and hematopoietic cancer was reported in a meta-analysis of 26 studies (meta-SMR 5 1.05, 95% CI: 0.92-1.21). 203 In a Swedish case-control study, NHL cases were significantly more likely to report exposure to ''high-grade'' organic solvents (OR 5 3.5, 95% CI: 1.7-7.1).…”
Section: Occupational and Environmental Chemical Exposurementioning
confidence: 99%
“…142 Other case-control studies that evaluated general classes of pesticides have reported odds ratios both above and below 1.0. 29,31,32,53,88,105,114,143 In a German case-control study that evaluated parental pesticide exposure and relative risk of NHL in children positive associations were observed with paternal and maternal exposure, based on small numbers. 144 Evaluating pesticides or categories of pesticides may obscure a chemical-specific association.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%
“…A number of cohort [33][34][35][36][37][38][39] and case-control 18,24,28,30,[40][41][42][43][44][45][46][47][48][49][50][51][52] studies have examined the relationship between cigarette smoking and multiple myeloma. Relative risk estimates for current cigarette smoking ranged from 0.8 to 1.3 in all cohort studies except the cohort of 34,000 California Seventh Day Adventists, which found a relative of risk of 6.79 (95% CI: 1.37, 33.61).…”
Section: Tobacco and Alcoholmentioning
confidence: 99%